2015
DOI: 10.1007/s12011-015-0396-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Supplementation on Antioxidant Defenses and Oxidative Stress Markers in Patients Undergoing Chemotherapy for Colorectal Cancer: a Placebo-Controlled, Prospective Randomized Trial

Abstract: The study aimed to investigate the effect of oral zinc supplementation on antioxidant defenses and oxidative stress markers during chemotherapy for colorectal cancer. Twenty-four patients who had undergone surgical resection of colorectal cancer participated in this placebo-controlled, prospective randomized study. The supplementation was started in the perioperative period, in which 10 patients received 70 mg of zinc (zinc group, n = 10) and 14 patients received placebo (placebo group, n = 14) for 16 weeks. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
1
19
0
7
Order By: Relevance
“…Golabek et al 41 Gallbladder activity, and the maintenance of vitamin E levels, although it had no effect on OS markers. 32 Besides, oral Zn sulfate supplements have been reported to improve the activity of Cu/Zn SOD enzyme in head and neck cancer (HNC) patients during radiotherapy. 37 A metaanalysis found that dietary Zn intake can considerably decrease the pancreatic cancer risk.…”
Section: CDmentioning
confidence: 99%
“…Golabek et al 41 Gallbladder activity, and the maintenance of vitamin E levels, although it had no effect on OS markers. 32 Besides, oral Zn sulfate supplements have been reported to improve the activity of Cu/Zn SOD enzyme in head and neck cancer (HNC) patients during radiotherapy. 37 A metaanalysis found that dietary Zn intake can considerably decrease the pancreatic cancer risk.…”
Section: CDmentioning
confidence: 99%
“…Alguns estudos não encontraram diferença nos níveis eritrocitários da SOD ao longo do tratamento em pacientes com câncer cólon-retal (Ribeiro et al, 2015) e mieloma múltiplo (Mehdi et al, 2013). Contrariamente aos nossos resultados, alguns estudos mostram menores níveis eritrocitários da SOD em pacientes com câncer cólon-retal (Gopčević et al, 2013) e nos portadores de melanoma (Gadjeva et al, 2008).…”
Section: Enzimas E Vitaminas Antioxidantes E Marcadores De Peroxidaçãunclassified
“…Nossos achados vão de encontro com os resultados observados nos pacientes com câncer de pulmão de pequenas células e não pequenas células (Kaynar et al, 2005) e no câncer cólon-retal (Ribeiro et al, 2015). Diferente dos nossos resultados, vários autores documentaram menores níveis de GPx em pacientes com câncer cólon-retal (Gopčević et al, 2013), mieloma múltiplo (Mehdi et al, 2013), câncer de esôfago e de estômago (Dursun et al, 2006) e entre aqueles com diferentes sítios tumorais (Mantovani et al, 2002), quando comparados aos indivíduos saudáveis.…”
Section: Enzimas E Vitaminas Antioxidantes E Marcadores De Peroxidaçãunclassified
See 2 more Smart Citations